E-governance and political modernization: An empirical study based on Asia from 2003 to 2014 - Shouzhi Xia (Administrative Sciences, 2017)
This study aims to analyze whether E-governance matters for political modernization in Asia. According to the literature review, E-gcovernance can be operated by three elements: open data, online service, and E-participation. Political modernization can also be divided into three elements: the government's transparency, the offline political participation, and the level of liberty. Analyzing second-hand data from several databases, this study draws such conclusions. Firstly, the development of E-governance will lead to the improvement of political modernization in Asia. Specifically, open data have a positive impact on the government's transparency. E-participation has a positive impact on the offline political participation and the level of liberty. Secondly, it is difficult to confirm which aspect of E-governance has the greatest impact on political modernization, as open data and E-participation have an impact on different aspects of political modernization. Based on the result, Asian countries should emphasize the importance of E-governance so that political modernization in this region could be improved continuously.
Keywords: 350; E-governance; political modernization; Asia